Examen especial a la cuenta cartera de crédito de consumo vencida de la cooperativa de ahorro y crédito de la pequeña empresa CACPE - Yantzaza (agencia los encuentros), del canton Yantzaza provincia de Zamora Chinchipe durante el periodo 2014 - Jiménez Jiménez, Mónica María (2016)
This thesis called: exam Special to the Loan Portfolio of credit of consumption expired of the CACPE-Yantzaza Agency (Los Encuentros), it realice como requisito previo to obtaining the engineering degree in Accounting and Auditing (CPA). It has met the goals tracings that consistienron in evaluate the efficiency and effectiveness of the internal control system in relation to the Loan Portfolio, the degree of compliance with laws, regulations and provisions applicable regulations was verified. Audit techniques and procedures applied in the records, vouchers, documents approval process Credit and recovery of nonperforming loans; the use of working papers that support the evidence of findings. The results are expressed in in this report. Among the main conclusion of the work done it is noted that the monitoring process is performed for the recovery of Loans, shortcomings failings for which becomes overdue loans. The manager of the cooperative is recommended comply with and enforce the Regulation of Credit of the company, Reglamento del Consejo, Law of Popular and Solidarity Economy of the Superintendency of Popular and Solidarity Economy, Standard Internal Control of the General Comptroller of the State applied to public and private sector, Financial Reporting Standards and Generally Accepted Accounting Principles, the same that allow him to maintain an efficient control of financial resources of the Cooperative, concerning the management of Portfolio Overdue Consumer of Credit.